Análise da adesão da população para implantação da pré-coleta nos sistemas de coleta seletiva de resíduos sólidos domiciliares da cidade de João Pessoa /PB - Pinheiro, Alba Valéria de Barros e Silva (2005)
The final disposition of the solid wastes is today considered one of major problems in the cities of average and big size. This fact has taken, to the city organs, a revision and improvement of the administration of theses residues not limiting its management merely to the collection and final disposition, but searching a systematic decrease of the production of residues in its source and, consequently, less environmental impact. Within the administration, the process of selective collection stands out which is characterized by the setting apart of residues, which may be recuperated in the generating source itself and which must have distinct conditioning for commercialization. In this kind of collection, the pre-collection phase (handling, conditioning and segregation) plays a relevant role for the citizen goes from a passive situation to an active role, as a processor of the materials in its source. In this way the aim of this work was to analyze the adhesion of the population of part of the city of João Pessoa to the implantation of the pre-collection in the Systems of Selective Collection of Domestic Solid Wastes, taking into account the receptivity of the population assisted, the problems and limitations of the system adopted and the proposal of incentives to the adhesion. The study was developed in the suburbs of Cabo Branco, Manaíra, Miramar e Tambaú which make part of Nucleus 1 of the selective collection in the city of João Pessoa PB, implanted since September, 2000 and supported by the City Special Autarchy of Urban Cleaning (EMLUR). The methodology used for the measurement of the awareness and participation of the population in the selective collection was the conduction of a survey with the households in Nucleus 1. The software Sphinx Plus2 was used for the statistic analysis of the data. The indicators of receptivity, awareness and participation of the population in relation to the program of selective collection and the proposed incentives by the research to the adhesion to the pre-collection program as well as the positive and negative points of the program were verified. Among the relevant results we can point out that 70,16% of the surveyed people are aware of the selective collection program; that among the 61,27% of the surveyed people who do the selective pre-collection, 77,40% had orientation to do it; that the adhesion to the pre-collection does not depend on the school level; that 94,92% of the surveyed people consider the selective collection beneficial; and that 55,87% chose, as a main incentive to adhere to the pre-collection, the placing of appropriate recipients for each kind of waste near the residence. Based on the results obtained it was observed that there was the need of more campaigns of divulgation and conscientiousness about the selective collection, with the purpose of motivating the participants and stimulating the adhesion of part of the population who is not yet inserted in the program